Evaluation of groundnut shell for enhancing geotechnical performance of weak soil - Basnet, Jhalak Man; Baidya, Purnima; Dahal, Bhim Kumar (Journal of Engineering Issues and Solutions, 2024)
This research delves into the persistent challenge of strengthening weak soil for infrastructural development, exploring the potential use of agro waste such as groundnut shell ash (GSA) as a soil improvement admixture. Through a comprehensive study on various geotechnical properties of soil, different proportions of GSA, both solely and as alkaline-activated were used. The investigation evaluated Atterberg’s limits, compaction characteristics, and unconfined compressive strength. Comparative analyses revealed the efficacy of these admixtures. Results indicated that alkaline-activated GSA demonstrated superiority across all geotechnical properties, notably transforming high-plastic soil into low-plastic soil, unlike GSA-only treatments, which altered specific properties but failed to induce the desired transformation. Both additives reduced the maximum dry unit weight but increased the optimum moisture content. The alkaline-activated GSA demonstrated a lesser decrease in unit weight. Moreover, this form of GSA enhanced the compressive strength of natural soil by 11.71 times at 10% GSA content, compared to the 2.2-fold increase achieved by soil treated only with GSA content of 6%. Therefore, the results indicated the use of GSA as viable agro waste for sustainable soil stabilization of soil deposits in Kathmandu Valley.